Perancangan Conveyor Pada Mesin Pengisi Botol Otomatis - Junaidi; R S Manullang; D A Ritonga (Jurnal MESIL (Mesin Elektro Sipil), 2022)
Technology continues to develop from time to time with all the innovations that aim to ease all human affairs, from the industrial world aspect. Human needs are increasing, developing and varying, to meet the needs of the industry requires a tool that can control and control the machining process automatically so as to simplify and save human labor, such as designing an automatic conveyor on an automatic bottle filling machine using a PLC (Programmable Logic Controller). With a PU (polyurethane) conveyor belt material that is rough, slippery and elastic, the surface of the belt conveyor works horizontally and can carry bottles at a conveyor speed that uses a 12v DC power window motor, a speed of 90 rpm and a torque of 3N.m without a load. The speed of the conveyor with a bottle distance of 1mm and has a time of 6.82 s, then the result of a one-way bottle speed is 0.146 m/s.